Anthropometric Analysis of the Dental Arches of Five-Year-Old Children With Cleft Lip and Palate. Issue 6 (September 2018) - Rando, Gabriela Mendonça; Ambrosio, Eloá Cristina Passucci; Jorge, Paula Karine; Prado, Danielle Zola Almeida; Falzoni, Maiara Miyuki Matsui; Carrara, Cleide Felício Carvalho; Soares, Simone; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
Abstract : Abstract: This study aimed to analyze the dimensional alterations of the dental arches of 5-year-old children with cleft lip and palate and to compare these dimensions with children without oral clefts. One hundred twenty children were divided into the following groups: unilateral cleft lip (UCL), unilateral cleft lip and palate (UCLP), cleft palate (CP), and control (C). A specific software was used to digitize the dental casts and perform the anthropometric analyses through the measurement of transversal linear intercanine and intermolar distances on the maxilla and mandible. The intergroup comparisons of the maxillary dimensions exhibited that the intercanine distances of groups C and UCL were statistically greater than that of groups UCLP and CP. The intermolar distance was significantly smaller in group UCLP than in the other groups. No statistically significant difference occurred in the mandibular intercanine and intermolar distance among groups. The analysis of the superposition of the maxillary over the mandibular transversal distances showed statistically significant differences among groups. This study showed that at 5-year old, the children with cleft involving the palate had more maxillary dimensional alterations than those without cleft palate.